Use of timelapse photography to determine flower opening time and pattern in banana (Musa spp.) for efficient hand pollination - Waniale, A.; Swennen, Rony L.; Mukasa, S.; Tugume, Arthur K.; Kubiriba, Jerome; Tushemereirwe, Wilberforce K.; Uwimana, Brigitte; Gram, G.; Amah, D.; Tumuhimbise, Robooni (Springer, 2021)
Sterility and low seed set in bananas is the main challenge to their conventional genetic improvement. The first step to seed set in a banana breeding program depends on pollination at the right time to ensure effective fertilization. This study aimed at determining bract opening time (BOT) to enhance efficient pollination and seed set in bananas. A Nikon D810 digital camera was set-up to take pictures of growing banana inflorescences at five-minute intervals and time-lapse movies were developed at a speed of 30 frames per second to allow real-time monitoring of BOT. Genotypes studied included wild banana (1), Mchare (2), Matooke (4), Matooke hybrid (1), and plantain (1). Events of bract opening initiated by bract lift for female flowers (P < 0.01) started at 16:32 h and at 18:54 h for male flowers. Start of bract rolling was at 18:51 h among female flowers (P < 0.001) and 20:48 h for male flowers. Bracts ended rolling at 02:33 h and 01:16 h for female and flowers respectively (P < 0.05). Total time of bract opening (from lift to end of rolling) for female flowers was significantly longer than that of male flowers (P < 0.001). On average, the number of bracts subtending female flowers opening increased from one on the first day, to between one and four on the fourth day. The number regressed to one bract on day eight before start of opening of bracts subtending male flowers. There was a longer opening interval between bracts subtending female and male flowers constituting spatial and temporal separation. Bract rolling increased from partial to complete rolling from proximal to the distal end of the inflorescence among female flower. On the other hand, bracts subtending male flowers completely rolled. Differences in BOT of genotypes with the same reference time of assessment may be partly responsible for variable fertility. Hand pollination time between 07:00 and 10:00 h is slightly late thus an early feasible time should be tried.